Genesis of the school physical education content in the social order context - Дейнеко, Альфія; Красова, Інна; Марченков, Михайло (Slobozhanskyi Herald of Science and Sport, 2017)
Alfiia Deineko, Inna Krasova & Mykhailo Marchenkov Purpose: to analyze the genesis of the content of school physical education in the context of social order, separating the features of the modern physical education program in the general educational institutions of Ukraine. On the basis of the use of chronological periodization in the article, the features of the content of the systems of school physical education are emphasized in connection with the contextuality of historical epochs. Material & Methods: analysis of special literature, which reveals the features of the content of school physical education in different historical epochs; chronological periodization; analysis of regulatory legal acts. Results: in the process of development of the system of school physical education, the curricula for physical culture also changed; there were contextual features of political, economic and social development of Ukraine during the last century. Conclusion: the dynamics of the content of physical education programs at the secondary school shows the growing differentiation and humanization of the system of physical education in modern Ukraine.